(untitled) (Journal of Environmental Bioremediation and Toxicology, 2024)
The increasing prevalence of extended-spectrum beta-lactamase-resistant (ESBL) Klebsiella pneumoniae in Malaysia is alarming. The lipopolysaccharide (LPS) of Klebsiella pneumoniae, particularly its lipid A moiety, plays a central role in the bacterium’s toxicological profile by inducing strong pro-inflammatory responses and contributing to septic shock in systemic infections. Morbidity and mortality associated with this condition are alarming. A comprehensive evaluation of the proportion of this phenomenon will aid the Malaysian government and health authorities in their efforts to reduce its burden. Hence, this systematic review and meta-analysis were conducted to evaluate the incidence of ESBL K. pneumoniae in Malaysian clinical and community infections. The study was conducted in accordance with the PRISMA guidelines and preceded by the development of an a priori protocol. The protocol was then registered in PROSPERO – the public registry for systematic reviews. Six important outcomes, including the assessment of the overall ESBL K. pneumoniae prevalence, were designed to be evaluated. A literature search was conducted in four selected electronic databases, and 310 articles were screened. Of these articles, only seven studies that met the eligibility criteria were included in the review. Relevant data were extracted from the included studies. By conducting a meta-analysis of quality effects, the pooled prevalence of ESBL K. pneumoniae in Malaysia was estimated at 72% (CI: 39-97). The review also identified ESBL gene types occurring mostly in infections. The high prevalence of ESBL K. pneumoniae in this study area is highly significant and of both public health and clinical relevance. Overall, the findings of this review will assist in the effective prevention and control of this threat in the study area.